The role of CRM and its influence on Corporate image and customer loyalty - Themistocleous, Christos (2011)
In this assignment we seek to capture the role and influence of Customer Relationship Management on corporate image and customer loyalty. We focus our analysis on the Bank of Cyprus(BoC) and the different mechanisms its CRM department used. Particular attention was paid on the personal banker mechanism and how its interactions with the customers can influence corporate image and induce customer loyalty. Once we identify how CRM affects customer loyalty and corporate image we make thorough recomendations to managers based on our findings.